2016
DOI: 10.1002/jcla.21990
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Long Noncoding RNAs are Differentially Expressed in the Cervicovaginal Lavage Samples of Cervical Cancer Patients

Abstract: Our data suggest that lncRNAs in exosomes isolated from cervicovaginal lavage are differentially expressed in cervical cancer patients and cancer-free volunteers. Exosomal lncRNAs may have great potential to be used for the early detection and diagnosis of cervical cancer, and serve as convenient and noninvasive biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 25 publications
(33 reference statements)
0
76
0
2
Order By: Relevance
“…In contrast, MEG-3 is down regulated in cancer patient lavage compared to the control group. Further analysis revealed that HPV infection might regulate the exosomal lncRNAs secretion, since the level of these transcripts varies between HPV positive patients and the negative control group (39). …”
Section: Exosome Lncrnas As Potential Cancer Biomarkersmentioning
confidence: 99%
“…In contrast, MEG-3 is down regulated in cancer patient lavage compared to the control group. Further analysis revealed that HPV infection might regulate the exosomal lncRNAs secretion, since the level of these transcripts varies between HPV positive patients and the negative control group (39). …”
Section: Exosome Lncrnas As Potential Cancer Biomarkersmentioning
confidence: 99%
“…98 Exosomes, which are an important part of the microenvironment, range in size from 40 to 150 nm and represent a subset of multi-vesicular bodies (MVB). [97][98][99][100][101][102][103][104][105][106][107] They are formed by inward budding of the limiting membrane of MVB and are released from the cell into the extracellular environment upon fusion of the MVB and the plasma membrane. Exosomes contain a concentrated group of functional molecules including proteins, lipids, mRNAs, non-coding RNAs and DNA molecules.…”
Section: Role Of the Microenvironment And Exosomes In Emt And Cscsmentioning
confidence: 99%
“…102 Other studies have shown that exosomes derived from cancer cells have an important role in premetastatic niche formation (Figure 1). [103][104][105][106][107] Peinado et al 103 showed in a series of elegant experiments that melanoma exosomes could educate bone marrow progenitor cells into a prometastatic phenotype through MET. The accumulating data would suggest that exosomes mediate communication at both the primary and metastatic tumor sites and that the content of the exosomes can induce a pro-tumorigenic niche and support cell transformation.…”
Section: Role Of the Microenvironment And Exosomes In Emt And Cscsmentioning
confidence: 99%
“…Exosomes are small membranous vesicles (30‐100 nm) present in all biological fluids . Exosomes carry proteins and genetic materials, including DNA, mRNA and noncoding RNA, capable of revealing genetic information related to their parent cells .…”
Section: Introductionmentioning
confidence: 99%